two new species of the genus Solanum L. (Solanaceae Juss.) for the flora of Vietnam - Hop, Vu Van; Phuong, Vu Xuan (Academia Journal of Biology, 2014)
This is the first time two species Solanum nienkui Merr.& Chun. and Solanum neogriffithii V. V. Hop, nom. nov. [Solanum griffithii (Prain) C. Y. Wu & S. C. Huang (1978), non Solanum griffithii Kuntze (1891)] (Solanaceae Juss.) have been discovered in Vietnam. The species Solanum nienkui Merr. & Chun differs from all other species of the genus Solanum known in Vietnam by its elongate racemose inflorescences with many flowers. The species Solanum neogriffithii V. V. Hop differs from all other species of the genus Solanum known in Vietnam by its calyx accrescent with dense stellate hairs and numerous short yellowish prickles, closely enveloping the most of the glabrous berry.